Probiotics Regulating Inflammation via NLRP3 Inflammasome Modulation: A Potential Therapeutic Approach for COVID-19 - Arezina N. Kasti (MDPI AG, 2021)
Inflammasomes are cytoplasmic multiprotein complexes formed by the host’s immune system as a response to microbial infection and cellular damage. Many studies have revealed various regulators of NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome activation, while it has been recently shown that NLRP3 is implicated in COVID-19 pathogenesis. At the same time, probiotics counteract the inflammatory process and modulate cytokine release, thus influencing both innate and adaptive immune systems. Herein, we review the immunomodulatory potential of probiotics on the assembly of NLRP3 inflammasome, as well as the pathophysiological mechanisms supporting the use of probiotic bacteria for SARS-CoV-2 infection management, presenting evidence from preclinical studies of the last decade: in vivo, ex vivo, and mixed trials. Data show that probiotics intake is related to NLRP3 inflammasome attenuation and lower levels of inflammation markers, highlighting the beneficial effects of probiotics on inflammatory conditions. Currently, none of the ongoing clinical trials evaluating the effectiveness of probiotics intake in humans with COVID-19 has been completed. However, evidence from preclinical studies indicates that probiotics may block virus invasion and replication through their metabolites, bacteriocins, and their ability to block Angiotensin-Converting Enzyme 2 (ACE2), and by stimulating the immune response through NLRP3 inflammasome regulation. In this review, the beneficial effects of probiotics in the inflammatory process through NLRP3 inflammasome attenuation are presented. Furthermore, probiotics may target SARS-CoV-2 both by blocking virus invasion and replication and by stimulating the immune response through NLRP3 inflammasome regulation. Heterogeneity of the results—due to, among others, different bacterial strains and their metabolites, forms, dosage, and experimental designs—indicates the need for more extensive research.